2020
DOI: 10.1177/1129729820913437
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound for assessing arteriovenous fistula maturity in outpatient hemodialysis

Abstract: Background: Point-of-care ultrasound in end-stage renal disease is on the rise. Presently the decision to cannulate an arteriovenous fistula is based on its duration since surgery and physical exam. This study examines the effects of point-of-care ultrasound on decreasing the time to arteriovenous fistula cannulation, time spent with a central venous catheter, and the complications and infections that arise. Methods: Prospective point-of-care ultrasound patients were recruited between January 2015 and January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Many clinical studies have shown that the most common causes for hospitalization of these patients are cardiovascular and cerebrovascular diseases, infections and access complications. 25,26 In the current study, the hospitalization rate of patients with AVF was lower than that of patients with CVC (P<0.05), suggesting that patients undergoing MHD with CVC might have a poor prognosis. Our results are consistent with Almasri et al 27 It is plausible that despite optimized biocompatibility, the catheter still carries a high risk of infection and access related complications as a central venous foreign body.…”
Section: Discussionmentioning
confidence: 48%
“…Many clinical studies have shown that the most common causes for hospitalization of these patients are cardiovascular and cerebrovascular diseases, infections and access complications. 25,26 In the current study, the hospitalization rate of patients with AVF was lower than that of patients with CVC (P<0.05), suggesting that patients undergoing MHD with CVC might have a poor prognosis. Our results are consistent with Almasri et al 27 It is plausible that despite optimized biocompatibility, the catheter still carries a high risk of infection and access related complications as a central venous foreign body.…”
Section: Discussionmentioning
confidence: 48%